Unlocking Sustainability through Supply Chain Visibility: Insights from the Manufacturing Sector of Bangladesh - Emon, Md Mehedi Hasan; Khan, Tahsina (Brazilian Journal of Operations & Production Management, 2024)
Goal: This research delves into sustainable supply chain management within the context of manufacturing companies in Bangladesh, aiming to unravel the complexities and dynamics of supply chain visibility (SCV), connectivity, and their influence on economic, social, and environmental performance. Design/Methodology/Approach: Employing a contingent Resource-Based View perspective, the study develops a hierarchical model, formulates hypotheses, and conducts analyses using Smart PLS 4. It explores the interplay between supply chain connectivity, information sharing, and product complexity in influencing sustainable supply chain performance. Findings: The study reveals that supply chain connectivity positively impacts information sharing, leading to enhanced SCV. SCV, in turn, positively influences economic, social, and environmental performance. Product complexity is identified as a moderating factor in this relationship. Research Limitations/Implications: While the findings offer valuable insights, the study's focus on manufacturing companies in Bangladesh implies contextual limitations. Future research could explore diverse settings and delve deeper into the specific mechanisms driving these dynamics. Practical Implications: This study offers actionable insights for manufacturing firms in Bangladesh, emphasizing the strategic adoption of advanced IT infrastructure to bolster supply chain connectivity. By fostering a culture of real-time information sharing through ICTs, companies can optimize operational efficiency. The research also underscores the importance of tailored approaches to product complexity, providing practical guidance for navigating diverse product portfolios. These practices collectively contribute to improved economic, social, and environmental performance, positioning companies as agile and responsible players in the global supply chain. Social Implications: The study underscores the broader social implications of sustainable supply chain practices, emphasizing the need for responsible and transparent operations that balance economic prosperity, environmental responsibility, and social considerations. Originality/Value: This research contributes to the existing body of knowledge by advancing our understanding of sustainable supply chain dynamics, particularly in emerging markets. It offers original insights into the contingent relationships between supply chain connectivity, information sharing, product complexity, and sustainable performance.